(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Almost all modern languages have an original language. This early language with all its derivatives forms a language "family". English belongs to the group of Indo-European languages. It also includes French, Italian, German, Norwegian and Greek. This article contains information about the emergence and at the same time the stages of development of the English language, in which period it was used by which peoples.